ANALISIS PERUBAHAN SIKAP PARTAI POLITIK GERINDRA DARI PARTAI OPOSISI MENJADI PARTAI KOALISI PASCA MASA PEMILU 2019 - Eva Faturjannah (2023)
This study aims to discuss the changes in the attitude of the Gerindra political party after the 2019 election period which chose to join the government coalition by using political party theory, rational choice theory and the concept of political interests. The research approach uses a qualitative approach, for this type of research is descriptive research. Sources of primary data and secondary data come from interviews and literature. The process of data analysis through data collection, data reduction, data presentation and drawing conclusions. The final results of this study indicate that the motivation of the Gerindra party is to join the government coalition. Rational choice theory is used to see that the motivation for joining the Gerindra Party is to gain the power of the Gerindra party through its cadres who are included in the current cabinet composition, then gain access to managing natural resources, especially in the defense and maritime sectors. Not only for the sake of the nation's interests. This change in attitude led to the formation of a pragmatic coalition which would result in threatening the sustainability of democracy due to the lack of parties outside the government as counterbalancers in a democratic system. Keywords: Gerindra Party, Coalition, and Opposition